Implementing the 3Rs in Laboratory Animal Research-From Theory to Practice - Azkona, Garikoitz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the latest advances in the field of the 3Rs, as applied to laboratory animals. The continuous progress in the application of the 3Rs will allow for us to achieve a more humane and equally competitive science, improving animal welfare.